The Inclusive Education Program in Jambi: Voices from Insiders - ROSMIATI ROSMIATI; ABDOEL GHAFAR; TABRONI TABRONI; ADITYA RAHMAN (Universitas Jambi, Indonesia, 2019)
This study was aimed at exploring the inclusive education programs developed by the government including inclusion-education curriculum, special mentor recruitment, and infrastructure facilities in the schools. The study used a qualitative method with a case-study tradition. The data were collected through interviews with 8 informants, 5 classroom observations, and documents at one elementary school. The interview data were analyzed using within-case and cross-case analyses among informants. The observational data were recorded and presented in accordance with the themes of the interview results and document data were used as the comparison. The results revealed that there were no new student admission preparation, and lack of government attention on infrastructure. The presentation of the data also included the challenges faced in implementing inclusive education. Suggestions and implications for schools in the implementation of inclusive education and the government are discussed.